2022
DOI: 10.1109/jbhi.2022.3198440
|View full text |Cite
|
Sign up to set email alerts
|

Customized Federated Learning for Multi-Source Decentralized Medical Image Classification

Abstract: The performance of deep networks for medical image analysis is often constrained by limited medical data, which is privacy-sensitive. Federated learning (FL) alleviates the constraint by allowing different institutions to collaboratively train a federated model without sharing data. However, the federated model is often suboptimal with respect to the characteristics of each client's local data. Instead of training a single global model, we propose Customized FL (CusFL), for which each client iteratively trains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…ML models are then trained using these centralized data. In contrast, FL aims to train AI models while keeping the data decentralized at multiple data collection sites [70,71]. In the mainstream FL framework, a centralized server coordinates the model training process.…”
Section: Multi-center Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…ML models are then trained using these centralized data. In contrast, FL aims to train AI models while keeping the data decentralized at multiple data collection sites [70,71]. In the mainstream FL framework, a centralized server coordinates the model training process.…”
Section: Multi-center Collaborationmentioning
confidence: 99%
“…The server aggregates these client model parameters into a single ML model. This approach enables collaborative model development and adaptation among multiple hospitals without the need to share any patient data [71][72][73][74][75][76][77]. FL has demonstrated reliable results when applied to clinical information, PET images, and multimodal data.…”
Section: Multi-center Collaborationmentioning
confidence: 99%
“…They introduced a new dataset called “DermaNet”, which consists of 23 diseases; however, they obtained a very low accuracy of 67% for the diagnosis of the skin diseases from this dataset. Other lightweight deep learning methods for melanoma detection are proposed [ 27 , 28 , 29 , 30 , 31 , 32 ], such as the method presented by Biasi et al [ 27 ]. The authors put forward a proposition for the creation and execution of a hybrid architecture that draws upon Cloud, Fog, and Edge Computing.…”
Section: Related Workmentioning
confidence: 99%
“…Wicaksana et al proposed Customized FL (CusFL) and demonstrated its ability to detect prostate cancer and identify skin cancer [89]. This group's approach differed from traditional FL by iteratively training a client-specific model based on the global model instead of training a single one, thereby avoiding catastrophic forgetting.…”
Section: Skinmentioning
confidence: 99%
“…Additionally, Sarma et al conducted a case study demonstrating their ability to utilize FL to train a deep learning model across three academic institutions while preserving patients' privacy [92]. Furthermore, Wicaksana et al, as mentioned in the skin section, proposed a new way to train the FL model and demonstrated the abilities of the said model on prostate cancer data [89].…”
Section: Prostatementioning
confidence: 99%